Preclinical Evaluation of the Copper-64 Labeled GRPR-Antagonist RM26 in Comparison with the Cobalt-55 Labeled Counterpart for PET-Imaging of Prostate Cancer - Baun C. Christina; Mitran B. Bogdan; Rinne S. S. Sara; Dam J. H. Johan; Olsen B. B. Birgitte; Tolmachev V. M. Vladimir Maksimilianovich; Orlova A. M. Anna Markovna; Thisgaard H. Helge (2020, 2020)
Title screen